Measles Surveillance Attributes Assessment Based on The Puskesmas Surveilance Officersâ Perception in Surabaya - Maharani, Bilqis Elfira; Hargono, Arief (Jurnal Berkala Epidemiologi, 2014)
ABSTRACTMeasles is one of infectious diseases that potentially lead to death when complications occur. Based on the data from East Java Health Department, Surabaya is the area where the most measles cases occur in East Java and increase in the last three years. As one of measles controlling efforts, surveillance has been expected to provide qualified data and information as the basis for any decision making for a treatment or intervention. Therefore, an evaluation is needed in order to assure the effectiveness and efficiency of the surveillance application in achieving the goals. This study is a descriptive research aiming at evaluating the attributes of measles epidemiology surveillance system in Surabaya onÂ 2012. The evaluation was done by assessing the attributes of surveillance then compared to Technical Guide for Measles Surveillance 2012, The Decree of The Health Ministry of The Republic of Indonesia No.1116/MENKES/SK/VIII/2003 On Guide for Conducting Surveillance System of Health Epidemiology and Guidelines for Evaluating Surveillance Systems from Center for Disease Control and Prevention 2001. The data collection method employed interview and observation or study documentation. The respondents of this study were 39 surveillance officers at 39 Puskesmas in Health Department Surabaya working area. The variabels of this study were simplicity, flexibility, data quality, acceptability, sensitivity, predictive value positive, representativeness, timeliness, and stability. The results of this study showed that the simplicity is complicated. The flexibility from CBMS is not flexible whereas the flexibility from EWARS is flexible. The data quality, acceptability, sensitivity and representativeness are low. The predictive value positive has not been able to be scored. The stability is high and the timeliness is punctual.Keywords: surveillance, evaluation, attribute, measles